Variability in Clinical Presentation of Neonatal Stroke: Report of Four Cases - Sonia Joseph; Dimitrios Angelis; Robert Bennett; Bhargavi Kola; Amanda Hughes (Case Reports in Neurological Medicine)
Neonatal stroke can be a cause of long term neurodevelopmental disability, seizures, and impaired cognitive function. We present four cases of neonatal stroke, associated with different risk factors and clinical presentations. Two of these newborns were born to mothers with no prenatal care.